UKURAN DASAR KELESTARIAN PRODUKSI PADA HUTAN RAKYAT DI KABUPATEN BARRU The Standard of Sustainable Production on Private Forest Management in Barru - Monisari Djamal; Hardjanto .; Yulius Hero (Jurnal Silvikultur Tropika, 2018)
Sustainable private forest management is an opportunition sustainable forest development in Indonesia. However, sustainable production of private forest management has not been known, because characteristics of private forest are different with state forest. This research aims to determine a relevant criteria and indicator of sustainable production on private forest management, case of Barru District. This research used descriptive explorative approach and quantitative-qualitative analysis. Criteria and indicator of sustainable production on Indonesia Community Based Forest Management was used as a reference to examine suitability of the standard on private forest management practice. The standards of sustainable production on sustainable private forest management consists of three criteria, namely: (1) sustainability of resources, the indicators were clearly land rights/status and boundaries, land cover change, intensity of planting, maintenance, and harvesting, (2) sustainability of yield, the indicator is infrastructure of forest management, and (3) sustainability of enterprise, the indicators were,market certainty, market accessibility, market information system, and contribution to social and economic improvement for local communities.Keywords: criteria, indicator, private forest, sustainable production.